2023
DOI: 10.1021/jacsau.3c00198
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Tetrahydrofurans in Thyclotides Enhances Oligonucleotide Binding and Cellular Uptake of Peptide Nucleic Acids

Abstract: Selective incorporation of conformational constraints into thyclotides can be used to modulate their binding to complementary oligonucleotides, increase polarity, and optimize uptake into HCT116 cells without assistance from moieties known to promote cell uptake. The X-ray structure and biophysical studies of a thyclotide–DNA duplex reveal that incorporation of tetrahydrofurans into an aegPNA backbone promotes a helical conformation that enhances binding to complementary DNA and RNA. Selective incorporation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Cyclopentane modified PNAs, developed at the Appella lab [ 29 , 30 ] are PNA monomers with a cyclopentane backbone. These cpPNAs have been shown to increase affinities of cpPNAs to complementary DNA and are promising antisense molecules [ 31 , 32 ]. In a recent study [ 33 ], we have shown that introducing cpPNA adjacent to the surrogate base (BisQ) in a model 11-mer FIT-PNA results in an impressive increase in quantum yield and brightness of these RNA sensors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopentane modified PNAs, developed at the Appella lab [ 29 , 30 ] are PNA monomers with a cyclopentane backbone. These cpPNAs have been shown to increase affinities of cpPNAs to complementary DNA and are promising antisense molecules [ 31 , 32 ]. In a recent study [ 33 ], we have shown that introducing cpPNA adjacent to the surrogate base (BisQ) in a model 11-mer FIT-PNA results in an impressive increase in quantum yield and brightness of these RNA sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that rigidifying the local environment of the surrogate base (BisQ) in a model FIT-PNA by introducing a cyclopentane-modified PNA monomer/s [ 31 , 32 ] adjacent to BisQ results in a substantial increase in the molecule’s brightness and quantum yield [ 33 ]. This strategy was recently shown to be translated for the detection of an mRNA in Plasmodium falciparum that is associated with drug resistance to the antimalarial drug, artemisinin [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peptide nucleic acid (PNA) was first reported three decades ago 1,2 and the field continues to draw attention from the community by virtue of its exceptional properties (for recent examples, see ref. 3–16). It is an artificial mimetic of DNA or RNA wherein the phosphoribosyl backbone has been replaced by a peptidic backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopentane-modified PNAs (cpPNAs) are PNA monomers with a cyclopentane backbone that have a defined stereochemistry. …”
mentioning
confidence: 99%